Fructose and glucose co-ingestion during prolonged exercise increases lactate and glucose fluxes and oxidation compared with an equimolar intake of glucose - Lecoultre, V.; Benoit, R.; Carrel, G.; Schutz, Y.; Millet, G. P.; Tappy, L.; Schneiter, P. (The American Journal of Clinical Nutrition, 2010)
When fructose is ingested together with glucose (GLUFRU) during exercise, plasma lactate and exogenous carbohydrate oxidation rates are higher than with glucose alone.